PESONA DAN KHARISMA USTADZ DALAM IMAJINASI POPULER DI INDONESIA - Chaniago, Rizky Hafiz (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2018)
The development of globalization and the present information age has influenced many relationships in the world of life, including the life of religiosity, especially Islam. Relation between religion and culture mainly through the development of popular culture in the era of globalization and information is characterized by various problems, dilemmas, and contradictions. In the millennium era in Indonesia the power of religion and the power of popular culture in the larger cultural context has led to various contradictions and paradoxes in religious life. The development of popular culture has had a profound effect on how religion is now understood and ritualized. To cite this article (7th APA style): Chaniago, R. H. (2018). Pesona dan Kharisma Ustadz dalam Imajinasi Populer di Indonesia [Ustadz's Enchantment and Charisma by Popular Imagination in Indonesia]. Journal Communication Spectrum, 8(1), 1-14. http://dx.doi.org/10.36782/ jcs.v8i1.1809